Nation-Wide Survey Assessing the Knowledge and Attitudes of Romanian Pharmacists Concerning Pharmacogenetics - Pop, Cristina; Cristina, Anamaria; Iaru, Irina; Popa, Stefan L.; Mogoșan, Cristina (Frontiers in Pharmacology, 2022)
Background: Pharmacogenetics (PGx) is an important component of personalized medicine that has the potential to improve medicines’ effectiveness and safety. However, despite progress in technology and availability, PGx testing application into patient-care in Eastern Europe countries, has been slow. Objectives: Our aim was to describe knowledge and attitudes of Romanian pharmacists concerning PGx, and identify potential factors limiting PGx implementation. Method: An anonymous, web-based questionnaire was distributed to Romanian pharmacists registered in the National Pharmacists’ Association (NPA) via an official e-mail sent by NPA representatives. Results: A total of 1058 pharmacists completed the questionnaires, resulting in a response rate of 7.56%. Pharmacists were predominantly female (90.08%), younger than 49 years (87.53%) and mostly worked in community pharmacies (80.19%). Most pharmacists (64.77%) had a knowledge score between 30 and 49 points out of 60, and (75.40%) had attitude scores between 9 and 7 out of 10. Attitude and knowledge scores positively correlated. Conclusion: Despite performing fairly well on general questions regarding PGx, Romanian pharmacists may lack in-depth knowledge, which can affect their readiness to discuss PGx information with patients or other healthcare professionals. High pricing was considered an important impediment in PGx testing implementation.